Mathew Brady portraits of a nation - Wilson, Robert 1951- (Bloomsbury, 2013)
"In the 1840s and 1850s, "Brady of Broadway" was one of the most successful and acclaimed Manhattan portrait galleries. Henry Clay, Daniel Webster, Dolley Madison, Henry James as a boy with his father, Horace Greeley, Edgar Allan Poe, the Prince of Wales, and Jenny Lind were among the dignitaries photographed in Mathew Brady's studio. But it was during the Civil War that he became the founding father of what is now called photojournalism and his photography became an enduring part of American history